(untitled) (College of Basic Education Research Journal, 2025)
Hittite Cuneiform Texts dating back to Second Millennium BC contain the oldest information about production of oil as an economic product and its consumption in daily life. Hittite texts show that the Anatolian region was famous for diversity of its agricultural products specially oily plants Researchers differentiated between oils and fats, according to Hittite laws, oil is a commercial product and traded for its high value. Oil and extracted animal fats were used for various and diverse uses, as rituals showed, meaning that oil entered into many areas of Hittite life. It was used as food as an ingredient of various types of Hittite dishes, also used as a medicinal substance with many therapeutic recipes, in addition to its uses in rituals for inauguration of king , rituals of military campaigns and everything related to religious aspects, not to forget to mention perfume industry. Research dealt with oils of various types and their multiple uses in Hittite Kingdom .